Morphine induces preconditioning via activation of mitochondrial K(Ca) channels - Fräßdorf, Jan (Springer-Verlag, 2010)
PURPOSE: Mitochondrial calcium sensitive potassium (mK(Ca)) channels are involved in cardioprotection induced by ischemic preconditioning. In the present study we investigated whether morphine-induced preconditioning also involves activation of mK(Ca) channels. METHODS: Isolated rat hearts (six groups; each n = 8) underwent global ischemia for 30 min followed by a 60-min reperfusion. Control animals were not further treated. Morphine preconditioning (MPC) was initiated by two five-minute cycles of morphine 1 μM infusion with one five-minute washout and one final ten-minute washout period before ischemia. The mK(Ca) blocker, paxilline 1 μM, was administered, with and without morphine administration (MPC + Pax and Pax). As a positive control, we added an ischemic preconditioning group (IPC) alone and combined with paxilline (IPC + Pax). At the end of reperfusion, infarct sizes were determined by triphenyltetrazoliumchloride staining. RESULTS: Infarct size was (mean ± SD) 45 ± 9% of the area at risk in the Control group. The infarct size was less in the morphine or ischemic preconditioning groups (MPC: 23 ± 8%, IPC: 20 ± 5%; each P < 0.05 vs Control). Infarct size reduction was abolished by paxilline (MPC + Pax: 37 ± 7%, P < 0.05 vs MPC and IPC + Pax: 36 ± 6%, P < 0.05 vs IPC), whereas paxilline alone had no effect (Pax: 46 ± 7%, not significantly different from Control). CONCLUSION: Cardioprotection by morphine-induced preconditioning is mediated by activation of mK(Ca) channels.